EDUCATIONAL STORY BOOK BASED ON TOLERANCE CHARACTER AS AN INNOVATION OF INTRODUCING MULTICULTURAL EDUCATION - Fatmawati, Laila; Khotijah, Ayu Siti; Erviana, Vera Yuli (Jurnal Penelitian Pendidikan, 2018)
Multicultural education is still very foreign to elementary school teachers and students. Need innovation in introducing multicultural education to elementary school students through educational story book. The aims of this study are: 1) developing educational story book based on tolerance character, 2) knowing the feasibility of the educational story book based on experts’ judgment, 3) knowing the responses of teachers and students after using educational story book. The development procedure adopted Borg and Gall model. Data collection techniques were questionnaires and interviews. Data analysis techniques was descriptive statistics and qualitative analysis of interactive model. Small group trial subject used six students in the 5th grade of Wirosaban Elementary School. While the large group trial used 20 students in the 5th grade of Pakel Elementary School. The results of the study are educational story book with the title "Berbeda tapi Sama (Divers but the Same)". The mean score of the experts’ assessment are from the learning material is 86,53, language expert is 87,5, and media expert is 88,33. The teacher response in the small group trial is 98,33 and the students’ response is 99,58. The teacher's response in the large group trial is 81,66 and the students response is 97,87. All assessments from experts, teachers, and students are in a very good category. It can be concluded that educational story book with the title "Berbeda tapi Sama " is very feasible to be used to introduce multicultural education in elementary school students.